2018
DOI: 10.2147/ieh.s151040
|View full text |Cite
|
Sign up to set email alerts
|

Innovation implementation in the context of hospital QI: lessons learned and strategies for success

Abstract: Abstract:In 1999, the Institute of Medicine (IOM) reported that 98,000 people die each year due to medical errors. In the following years, the focus on hospital quality was intensified nationally, with policymakers providing evidence-based practice guidelines for improving health care quality. However, these innovations (evidence-based guidelines) that were being produced at policy levels were not translating to clinical practice at the hospital organizational level easily, and stark variations continued to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The data supports the original Innovation Implementation Framework, 42,44 specifically the importance of management support (coordinated organizational communication on the rationales and priority to establish CDC); implementation policies and practices (Procedures to set up CDC and proposal for CDC operation); implementation climate (responding to changing disease patterns, avoiding fragmentation, compliance to Party Resolution); and values fit (best practice of international model). The findings are also consistent with other studies 39,41,44,51 and also show that different elements of the framework are clearly inter-related. For example, values fit by the staff from the preventive medicine centers determine the implementation climate at the province level and together with management support from the MOH and province health department contribute to the effectiveness and speed of implementation of the MOH policy of an establishment of a provincial CDC network.…”
Section: Initial Implementation Of Policy On Provincial Cdc Establishsupporting
confidence: 93%
See 3 more Smart Citations
“…The data supports the original Innovation Implementation Framework, 42,44 specifically the importance of management support (coordinated organizational communication on the rationales and priority to establish CDC); implementation policies and practices (Procedures to set up CDC and proposal for CDC operation); implementation climate (responding to changing disease patterns, avoiding fragmentation, compliance to Party Resolution); and values fit (best practice of international model). The findings are also consistent with other studies 39,41,44,51 and also show that different elements of the framework are clearly inter-related. For example, values fit by the staff from the preventive medicine centers determine the implementation climate at the province level and together with management support from the MOH and province health department contribute to the effectiveness and speed of implementation of the MOH policy of an establishment of a provincial CDC network.…”
Section: Initial Implementation Of Policy On Provincial Cdc Establishsupporting
confidence: 93%
“…Innovation implementation in a healthcare setting refers to the implementation of anything new to the organization, be it an evidence-based practice, policy, or technology. 39 Adoption of innovations in healthcare has been widely accepted as a complex, organizational process that is much more humanistic than mechanistic. 40 The review of innovation implementation in the context of healthcare setting, identified as the "Innovation Implementation Framework," originally developed by Klein et al in 1996 and refined by Helfrich et al in 2007, was a popular theoretical framework used to explain factors driving innovation implementation success, particularly in works that sought it retrospectively.…”
Section: Theory: An Implementation Science Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism should facilitate tacit knowledge exchange on issues experienced with current practices, as well as possible resolutions to those issues.Conduct proactive, periodic communications (from senior leadership) on benefits of adhering to best practices and consequences of not adhering to them.Create shared understanding of the value of best practices (ie, the link between practices and outcomes) or the answer to the question of “why” practices need to change, to gain provider engagement in changing practices, before embarking on IT-training of providers to address sociotechnical challenges.Develop capacity to collect, analyze, and disseminate data on best-practice measures among providers to promote a scientific (research-based) approach to learning and improvement.Enable champions for change to emerge from among providers, to voice the need for culture change for enabling successful best-practice implementation; and reinforce these messages with proactive, periodic communication from senior leadership.Create a “learning health system,” by synthesizing lessons learned to facilitate “collective learning (aha) moments” across provider subgroups and care settings; and encourage providers to spread the learning within the broader institution. Management research has suggested framing practice issues as a “learning challenge” rather than a “performance challenge,” and addressing them in the form of non-threatening pilot research projects, to engage providers in improvement 32 , 33. This project fulfilled both criteria to demonstrate meaningful results.…”
Section: Discussionmentioning
confidence: 99%